The given equation is
![p^2+4p=1](https://img.qammunity.org/2023/formulas/mathematics/college/td0hxjxb6rqzl3v501ej0m06vzp6h2g3fe.png)
To use the completing square, divide 4p by 2 to find the product of the 2 terms of the bracket
![(4p)/(2)=2p](https://img.qammunity.org/2023/formulas/mathematics/college/imhcdl7cfgitkweo9a8blp0omzpptmnkg4.png)
Since 2p = 2 x p, then the bracket is (p + 2)
Let us make it power 2 and state its terms
![\begin{gathered} (p+2)^2=(p)(p)+(p)(2)+(2)(p)+(2)(2) \\ (p+2)^2=p^2+2p+2p+4 \\ (p+2)^2=p^2+4p+4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/c4aikc26jh7xhdy757fjpa54udnr2w5icx.png)
We have already p^2 and 4p, then we must add 4, then
Add 4 to both sides of the equation
![\begin{gathered} p^2+4p+4=1+4 \\ (p+2)^2=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/f8vzu38yymkgkfmls0ya7t1z84kpv2f3o9.png)
Now, let us take the square root to both sides
![\begin{gathered} \sqrt[]{(p+2)^2}=\pm\sqrt[]{5} \\ p+2=\pm\sqrt[]{5} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/odz8pkn03nbrh2ruttlhzwa6pjflqpvigb.png)
Subtract 2 from both sides
![\begin{gathered} p+2-2=\pm\sqrt[]{5}-2 \\ p=\pm\sqrt[]{5}-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gsyan4xvtnqylo1uyma2caa0smo42cme17.png)
The solutions of the equation are
![p=\sqrt[]{5}-2,p=-\sqrt[]{5}-2](https://img.qammunity.org/2023/formulas/mathematics/college/ihv7hd16mujh73sw5sbvpxbase0flxbvr3.png)